Pertumbuhan Dan Kadar Klorofil Tanaman Pakcoy (Brassica rapa L.) Terhadap Cekaman NaCl - V. Andriani (FMIPA : Universitas PGRI Adi Buana, 2017)
Gravity salt is a soil condition with excessive amounts of soluble salt and adversely affecting plant growth. A number of agricultural crops are able to survive in areas with high salt. This study aims to determine the growth and content of packed chlorophyll packed NaCl at the beginning of the vegetative phase, and determine how optimal concentration in the growth of pakcoy. The research was conducted in experimental garden and basic laboratory of Faculty of Mathematics and Natural Sciences UNIPA Surabaya. The research design was using Random Random Complete with NaCl stress treatment variation. Variation of low NaCl stress treatment consisted of control watered with water (N0), initial NaCl 50 mM + continued 150 mM (N1), initial NaCl 75 mM + continued 150 mM (N2), initial NaCl 100 mM + continued 150 mM (N3), initial NaCl 125 mM + continued 150 mM (N4), and initial NaCl 150 mM + continued 150 mM (N5). Parameters observed were plant growth (plant height, leaf number, leaf width, and root length and biochemistry (leaf chlorophyll) .The quantitative data obtained were analyzed using ANOVA and followed by DMRT test at 95% confidence level.The results showed that the NaCl stress treatment low at the beginning of the vegetative phase raising the height of the plant, the number of leaves, leaf width, root length and the highest leaf chlorophyll content in N1. Keywords: NaCl stress, pakcoy, growth, chlorophyll, vegetative phase